Efektivitas Pemungutan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan dalam Peningkatan Pendapatan Asli Daerah (Studi Kasus di Bappenda Kabupaten Bogor) Tahun 2018 - Zakia Mufliha; selvi selvi (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study was to analyze the effective level of Land and Building Tax Collection in Rural and Urban Areas, analyze the obstacles in the tax authorities in the implementation of Land and Building Tax Collection in Rural and Urban Areas, and analyze the efforts made by the tax authorities in overcoming obstacles. This study uses a Qualitative Approach with observation and interview techniques with Planning and Development staff, staff of Land and Building Tax in Rural and Urban Areas at the Regional Revenue Management Agency, academics and taxpayers. The results of this study are that the level of effectiveness of Land and Building Tax in Rural and Urban Areas in 2015-2018 is quite effective. The obstacle faced is that there are still many delays of taxpayers in paying Land  and  Building  Tax  in  Rural  and  Urban  Areas  each  year  and  the  lack  of  oversight  of  the Notification of Tax Due that has not yet been paid and for this condition the effort of  Regional Development Planning Agency in dealing with these obstacles are by conducting socialization to the public and increasing the number of mobile tax vehicles for rural areas. Suggestions for the results of this study are that the government should do more active and creative collection.